2020
DOI: 10.3390/rs12213526
|View full text |Cite
|
Sign up to set email alerts
|

Global-Scale Patterns and Trends in Tropospheric NO2 Concentrations, 2005–2018

Abstract: Nitrogen dioxide (NO2) is an important air pollutant with both environmental and epidemiological effects. The main aim of this study is to analyze spatial patterns and temporal trends in tropospheric NO2 concentrations globally using data from the satellite-based Ozone Monitoring Instrument (OMI). Additional aims are to compare the satellite data with ground-based observations, and to find the timing and magnitude of greatest breakpoints in tropospheric NO2 concentrations for the time period 2005–2018. The OMI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(23 citation statements)
references
References 45 publications
1
22
0
Order By: Relevance
“…This work was based on the data of the regional environmental agency: a survey on ozone and nitrogen dioxide at Passo Valles Therefore, even if it was not possible to know the NO 2 concentration at MRG, the mean values measured at Passo Valles suggest that a few ppb of NO 2 may have interfered with our experiment in MRG. Nevertheless, since it has been observed that the NO 2 concentrations are decreasing all over Europe (Jamali et al, 2020;Castellanos and Boersma, 2012), it is unlikely that NO 2 interference could have been detected by our LCSs system in MRG and thus explain some of the bias we observed between the LCSs and the reference instrument.…”
Section: Reliabilitymentioning
confidence: 86%
“…This work was based on the data of the regional environmental agency: a survey on ozone and nitrogen dioxide at Passo Valles Therefore, even if it was not possible to know the NO 2 concentration at MRG, the mean values measured at Passo Valles suggest that a few ppb of NO 2 may have interfered with our experiment in MRG. Nevertheless, since it has been observed that the NO 2 concentrations are decreasing all over Europe (Jamali et al, 2020;Castellanos and Boersma, 2012), it is unlikely that NO 2 interference could have been detected by our LCSs system in MRG and thus explain some of the bias we observed between the LCSs and the reference instrument.…”
Section: Reliabilitymentioning
confidence: 86%
“…The spatial distribution of artificial and natural vegetation restoration strategies was identified using the DBEST method. Jamali et al (2015) proposed the DBEST program for analyzing vegetation time series, which has been applied to the time series breakpoint detection of vegetation or other factors in different regions (Jamali et al, 2020; Shen et al, 2018; York et al, 2020). Combining the DBEST method with the identification of vegetation restoration strategies is an expansion of the application fields of the DBEST method that also provides methodological support for the visualization of ecological policy data.…”
Section: Discussionmentioning
confidence: 99%
“…NOx emissions in China significantly increased due to rapid industrialization, economic growth, and urbanization during the two decades before the 2010s [6][7][8], but started to decrease in the early 2010s [9,10] due to the effectiveness of China's Clean Air Action [11,12]. In particular, NOx emissions in eastern China from the Multi-resolution Emission Inventory for China (MEIC) decreased by 21% in 2017 relative to 2013, which is a smaller decrease than the 30% decrease observed by the Ozone Monitoring Instrument (OMI) in NO 2 columns over the same region during the same period [11].…”
Section: Introductionmentioning
confidence: 99%